Childhood cancer survival in Romania—A national pediatric registry perspective - Bucurenci, Mihaela; Zhang, Li; Wayne, Breana; Soliman, Amr; Neaga, Alexandra (Frontiers in Cancer Control and Society, 2025)
IntroductionPediatric cancer survival is increasing over time in European countries. However, there are survival differences in survival between Eastern and Western European member countries. The available mortality data based on the Romanian National Statistics Institute reports to Eurostat place Romania among the European countries with the highest child cancer mortality rates. The current study aims to investigate pediatric cancer survival and mortality outcomes in Romania, using the Romanian national-level cancer registry data. The Registry results add to the literature to illustrate the profile of pediatric cancers in Eastern Europe.MethodsThe study included 4,144 cancer patients aged 0–19 years, whose data were collected in the Romanian National Pediatric Oncology and Hematology Registry. These data comprise all the new cases diagnosed in Romanian pediatric cancer facilities from January 1, 2010, to December 31, 2019. Survival probabilities were examined according to patient characteristics, such as tumor type, demography, geography and place of residence. The Chi-square test (Fisher Exact Test) was used to compare patients' personal and clinical characteristics by rural/urban designation. The Cox proportional hazards regression model was used to estimate the hazard ratios and 95% confidence intervals by rural/urban designation, economic development region, and selected cancer subtypes, according to the International Classification of Childhood Cancer, 3rd edition. The mean follow-up time was 6.09 ± 3.84 years. To calculate the 5-year survival rates, the study period ended on December 31, 2017, and the sample size was restricted to 3,308. A predictive model using multivariable logistic regression was used to assess the age group and rural-urban survival probabilities as well as survival probabilities for major cancer subtypes.ResultsThe 5-year overall survival probability for the 0–14 and 15–19 age groups was 73% (95% CI: 71, 75) and 69% (65%, 72%) respectively. Categorized further by smaller age groups for the 0–14 age group, the survival rates were 75% (0–4 years), 73% (5–9 years) and 69% (10–14 years). Hodgkin lymphoma (92%), nephroblastoma and other nonepithelial renal tumors (89 %), and lymphoid leukemias (80%) had the highest survival rates among all the seven major cancer subtypes in the 0–14 years population. The worst survival was observed for CNS tumors (62%), rhabdomyosarcoma (62%), neuroblastoma (67%), and bone tumors (52%). As compared to pediatric cancer patients residing in urban areas, significantly more rural patients died from cancer (32.6% vs. 22.4%, p < 0.0001).Discussion/conclusionThis is Romania's first pediatric cancer survival study based on well-validated national cancer registry data. The Romanian Pediatric Cancer Registry continues to shed light on the profile of pediatric cancers in Romania. Overall survival rates in Romania were lower than survival rates reported from the EU-15 countries. Rural patients had lower survival than urban patients. Future studies should investigate the relationship between patients' clinical and socioeconomic characteristics and survival outcomes. Further research is also needed to investigate recurrence and secondary malignancies among this population.